Manfaat Membaca Cerita Dongeng Kancil yang Berjudul : Kisah Kancil dan Buaya untuk Anak dalam Membentuk Karakter - Revika Angeli Febrina; Herlinda Herlinda (BADAN PENERBIT STIEPARI PRESS, 2025)
The story of Kancil and Crocodile is a fairy tale that is often read by children. This study analyzes the moral impact of the fairy tale